The Relationship Between Nationalism and Historical Awareness - Mahfud, Muhammad Hasmal; Hariyono, Hariyono; Widiadi, Aditya Nugroho (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The interaction between nationalism and historical awareness is very close and strong. Many writings make both of them the result of historical learning. This attitude of love and sense of belonging to one's homeland is closely related to the growth of historical awareness in citizens. With the spirit of nationalism, identity and cultural continuity will be maintained, this is due to a feeling of love for every work of one's nation, as well as a sense of appreciation for one's nation's past as the navigator of the ship of a nation's journey. The purpose of writing this article is to explain the actual relationship between nationalism and historical awareness. The method used is the library method. The results of the research show that nationalism and historical awareness have a very close relationship and are inseparable from each other and cannot be developed without one of them.